Assessment of the two-phase thermosyphon loop with high filling ratio under anti-gravity. (1st June 2023) - He, Yichuan; Hu, Chengzhi; Hu, Xianfeng; Xu, Haochen; Tang, Dawei
Highlights: Thermal characteristics of a loop thermosyphon under anti-gravity are studied. The operation principle under anti-gravity is discussed. The influence of inclination angles and cooling water temperature are investigated. Abstract: In various fields of thermal management and protection, such as vehicles, aircraft, and mobile electronic devices, it is crucial to transfer heat effectively from the top to the bottom. The use of a simple structure for this transfer can reduce the weight of the heat transfer system. Theoretical studies have demonstrated that the two-phase thermosyphon loop (TPTL) with a high filling ratio has the potential for excellent performance in anti-gravity applications. In this study, we investigate the thermal performance of a high filling ratio TPTL under anti-gravity conditions. Our results reveal that, contrary to previous understanding, a TPTL with a high filling ratio can effectively transfer heat in anti-gravity. However, we also found that the loop thermal resistance of TPTL under anti-gravity is greater than under gravity, and the heating surface temperature is higher. Additionally, we experimentally study the effect of inclination angles on anti-gravity performance, and our results indicate that smaller angles result in better heat transfer. Finally, we investigate the impact of cooling water temperature on thermal performance. Overall, considering the energy efficiency of the heat dissipation system and the heat transfer capacity of the device, it is not recommended to use cooling water at a lower temperature. This research sheds light on the potential for TPTLs to operate in anti-gravity conditions and supports their practical applications.